A synopsis of Meriania (Melastomataceae: Merianieae) in Peru - Fernandez-Hilario, Robin; Goldenberg, Renato; Michelangeli, Fabián A. (Phytotaxa, 2023)
A synopsis of the genus Meriania in Peru is presented here, where 36 species are recognized, 25 of which are endemic. This synopsis includes a key to the genera in the tribe Merianieae, a key to the recognized Meriania species for Peru, illustrations, comments on affinities, distribution and phenology, and nomenclatural notes. Peru is now the country with the second highest diversity of the genus. The departments in Peru with the highest number of species are Amazonas (18 species), Cajamarca (11 species) and San Martín (9 species), and 24 species are located within Amatope-Huancabamba Zone in northern Peru. Meriania in Peru is characterized by being trees and shrubs, lacking malpighiaceous trichomes, inflorescences panicles or rarely dichasia, or solitary, (4–)5–6-merous flowers, usually large, with lobed, subcalyptrate or calyptrate calyces with regular, irregular or circumscissile dehiscence, spreading to campanulate corollas, stamen connectives with dorsal and dorso-basal appendages, anthers usually with a dorsally inclined pore, and capsular fruits. We propose one new combination, Meriania sessilifolia (Cogn.) Rob.Fern., R.Goldenb. & Michelang. Lectotypes for Axinaea purpurea, Centronia sessilifolia. Graffenrieda acida, Meriania prunifolia, M. raimondii, M. rigida, M. rugosa, M. spruceana and Pachymeria rigida are also designated.